Delivery systems for biopharmaceuticals. Part II: liposomes, micelles, microemulsions and dendrimers - Silva, Ana Catarina (2020)
Biopharmaceuticals are a generation of drugs that include peptides, proteins, nucleic acids and cell products. According to their particular molecular characteristics (e.g. high molecular size, susceptibility to enzymatic activity), these products present some limitations for administration and usually parenteral routes are the only option. To avoid these limitations, different colloidal carriers (e.g. liposomes, micelles, microemulsions and dendrimers) have been proposed to improve biopharmaceuticals delivery. Liposomes are promising drug delivery systems, despite some limitations have been reported (e.g. in vivo failure, poor long-term stability and low transfection efficiency), and only a limited number of formulations have reached the market. Micelles and microemulsions require more studies to exclude some of the observed drawbacks and guarantee their potential for use in clinic. According to their peculiar structures, dendrimers have been showing good results for nucleic acids delivery and a great development of these systems during next years is expected. This is the Part II of two review articles, which provides the state of the art of biopharmaceuticals delivery systems. Part II deals with liposomes, micelles, microemulsions and dendrimers.